STRUCTURE AND LEO TOLSTOY’S WORLDVIEWS IN 'ANNA KARENINA' FILM: A STUDY OF GENETIC STRUCTURALISM - Lismalinda Lismalinda; Budi Rizka (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2021)
This study aims to figure out the structure of Anna Karenina’s film and Leo Tolstoy’s worldview that is manifested in the film. This study utilizes the theory of genetic structuralism by Lucien Golman. This qualitative research is focused on the dialog of the movie and the author's social life. In order to complete the research, researchers have to go through a number of steps. The researcher first carefully watched the film and then collected some excerpts from the dialogue of the movie. Furthermore, the researcher reads several references to gain some information about the author's social life. The result of this study showed that the film 'Anna Karenina' expresses a Feminist-Liberal worldview. The social structure was dominated by the lower bourgeoisie, specifically Russian women, which hampered the development of material family life in accordance with modern society standards at the time.